The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fgwh.2022.999860
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need for contraception among married adolescent girls and young women in Haramaya Health and demographic surveillance system, Eastern Ethiopia

Abstract: BackgroundThe prevalence of unmet need for contraception is the highest in low- and middle-income countries (LMIC). Contraceptive use among young married or unmarried women is lower than that among older women in developing countries. Previous studies generalized the findings to all women of reproductive age and have not investigated psychosocial factors that influence contraceptive use. This study aimed to identify factors associated with unmet need for contraception among young married women in the Haramaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…This can be explained by the opposition that these AGYW are likely to face from their partners regarding modern contraceptive use. Other studies have demonstrated that married AGYW unsupported by their partners on modern contraceptive use, are likely to have higher unmet need [ 38 ]. Further, we also observed that sexually active AGYW (in the past 4 weeks) have a higher unmet need compared to their counterparts, possible explanation for this finding is that sexually active AGYW are likely to be married and even though they are willing to use modern contraception methods, they are likely to be hindered by their partners’ preferences or negative attitude toward contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the opposition that these AGYW are likely to face from their partners regarding modern contraceptive use. Other studies have demonstrated that married AGYW unsupported by their partners on modern contraceptive use, are likely to have higher unmet need [ 38 ]. Further, we also observed that sexually active AGYW (in the past 4 weeks) have a higher unmet need compared to their counterparts, possible explanation for this finding is that sexually active AGYW are likely to be married and even though they are willing to use modern contraception methods, they are likely to be hindered by their partners’ preferences or negative attitude toward contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…Research among young people in Ethiopia has found significant unmet SRH needs. Unmet need for family planning was estimated at 16% among all women ages 15-49 in 2019, and studies have found this number may be higher for adolescents and young women (18,19). In 2016, the median age at first intercourse was 16 years old, with more than half of young people having intercourse before the age of 18 (20).…”
Section: Introductionmentioning
confidence: 99%